Community Based Risk Behaviour Study on HIV/AIDS Targeting Women in Nepal - 2007 - Jha, KK; Salhotra, VS; Weerakoon, AP; Shrestha, L; Malla, P (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Nepal has progressed from a HIV low prevalence country to one with a concentrated epidemic in certain subgroups of population. It has been documented that girls and women are more vulnerable to HIV infection. However there is little documented evidence on the risk behaviour among women in Nepal. This study was conducted to assess the pattern of risk behaviour for HIV among women in Nepal. Methodology : The main component of the study comprised a community based cross-sectional study, using a multi stage random sampling technique. Data was collected by trained field health workers using an interviewer administered questionnaire. Eight focus group discussions were also conducted to supplement the findings. Statistical analysis was carried out using SPSS version 13. Results : A significant number of un married (13.7%) women and 2.2% of married women indulged in high risk sexual behaviour. A significant positive association was observed between sexual risk behaviour of married women and monthly family income less than 5000 Nepali Rs ,age group 25-34y and young age group (15- 34) in unmarried women. Nearly 70% of participatory women have heard about AIDS and have satisfactory level of knowledge about HIV/AIDS. However, significant number of respondents had misconceptions that one could contract HIV through hand shaking, mosquito bites and hugging. Using Condoms during unprotected sexual intercourse in both married and unmarried women were low (19.4% and 6.2% respectively). Findings of Focus Group Discussions revealed there is a strong stigma associated with HIV/AIDS in this rural community in Nepal. Conclusions : One in every seven unmarried woman in Nepal indulged in high risk sexual behaviour, which is much more compared to married women. There is an urgent need for reproductive health education especially among teenagers and for the National HIV/AIDS Control Programme to expand its awareness generation activities. Keywords : HIV/AIDS, women, risk behaviour, Nepal DOI: 10.3126/saarctb.v6i2.3051 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (2) 1-10